(untitled) (European Journal of Marketing and Economics, 2024)
Purpose: This paper investigates the key factors influencing Jordanian consumers’ decisions to switch from Internal Combustion Engine Vehicles (ICEVs) to Hybrid Electric Vehicles (HEVs) during the period of 2010-2014. Design/methodology/approach: A self-administered survey was distributed to car users across Jordan, yielding 333 valid responses from an initial sample of 400, demonstrating a high response rate of 83.25%. Findings: The study found no significant gender-based difference in switching behavior. Fuel consumption efficiency emerged as the primary driver for switching to HEVs, followed by eco-friendliness, lower taxes, and advanced technological features. Conversely, price and market trends were the least influential supporting factors. Major impediments to HEV adoption included concerns about battery life, limited market choices, insufficient information, and apprehension regarding the relatively new technology. Research limitations/Implications: Future research should explore additional factors such as perceived image, trust, and subjective norms, along with the evolving importance of environmental awareness and new technologies. Comparative international studies could offer valuable insights for cross-cultural consumer behavior analysis and global marketing strategies. Practical implications: The findings provide crucial insights for marketers to address consumer concerns by enhancing information dissemination and building awareness about HEV technology’s societal and environmental benefits. Originality/value: This study is among the first in Jordan to specifically examine customer switching behavior in the context of vehicle technology. It contributes to consumer behavior literature by elucidating the determinants of switching towards hybrid vehicles and their role in the consumer decision-making process.